Tourism and poverty alleviation in Tibet, China: the role of government in enhancing local linkages. Issue 2 (1st February 2022) - Ji, Zhongjuan; Xu, Honggang; Cui, Qingming
ABSTRACT: This study analyses the formation mechanism, poverty alleviation effects of local linkages, and examines the different agencies involved in shaping linkages in the Tibet Autonomous Region to understand local linkages in pro-poor tourism. A local linkage analysis framework composed of forward and backward linkages is developed from a value chain perspective. Research findings revealed the key role of governmental intervention in promoting diverse linkages, primarily forward local linkages. These linkages enable residents to occupy an active position in the tourism value chain, with improved participation and income in the tourism industry with the eventual outcome of poverty alleviation.